Unexpected Cost of Korean Wave during Pandemic Covid-19 in Makassar, South Sulawesi - Jerliyen Pramita Londong; Mira La'bi Bandhaso; Jane Lintang (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Kristen Indonesia Paulus, 2023)
This study discuss phenomenal success Korean Wave during pandemic covid-19 in Makassar, South Sulawesi, Indonesia. In recent years, Korean wave has become an addiction to young people in Makassar. This paper aims to explore the young people’s habit during pandemic covid-19, how they spend their leisure time throughout large scale social restriction (PSBB). Through the process of interviews, questionnaires, media, and article, this study result that the young people are willing to pay more to fulfill their hobby of watching Kdrama.